Makna Hospitality dalam Pembentukan Budaya Pelayanan Rehat Coffee and Space Cabang Condet - Isalsa Yudisti Sabila; Hilda Sari Wardhan; Pradnya Sari Harsanti (CV Global Research Publication, 2026)
Competition among coffee shops depends not only on products and atmosphere but also on consistent service that makes customers feel welcomed and valued. This study examined hospitality from the perspectives of a supervisor, employees, and customers at Rehat Coffee and Space, Condet Branch. The study was fully qualitative and phenomenological, conducted in June-July 2026 with one supervisor, five employees, and ten purposively selected customers. Interviews generated 160 response units and were analyzed using Colaizzi’s method, supported by observation, documentation, source triangulation, and member checking. The supervisor emphasized warm acceptance and personalization, while employees emphasized fast, accurate, responsive service and service recovery. Customer data comprised 61 units of positive-responsive experiences, 34 units concerning inconsistent greetings, warmth, and information, and 5 units concerning process and facility improvements. These frequencies demonstrate qualitative coding traceability rather than statistical measurement. The conceptual finding is hospitality congruence, alignment between intended, enacted, and perceived service through operational reliability and relational warmth. This alignment strengthens service-culture consistency and customer comfort. The findings provide a basis for evaluating service interactions, service recovery, and continuous service-quality improvement.